Life-Cycle Cost Analysis in Pavement Management System - Mikolaj, Jan; Schlosser, Frantisek; Remek, Lubos (Communications - Scientific letters of the University of Zilina, 2013)
Pavement Management System (PMS) is a set of methods and tools which allow for optimal allocation of limited resources while keeping the road network in serviceable condition. The system evaluates the viability of all maintenance, rehabilitation and reconstruction (MR&R) actions; the evaluation is a comparison process between procurement cost of MR&R action and benefits, which are achieved by the new, more favourable, serviceability conditions attained as a result of this particular action. The investment cost − procurement costs of MR&R action − are evaluated in terms of economical effectiveness by means of Life-Cycle Cost Analysis (LCCA).